2007
DOI: 10.1080/07370010709336582
|View full text |Cite
|
Sign up to set email alerts
|

The Health of Female Child Care Providers: Implications for Quality of Care

Abstract: The purpose of this investigation was to determine the health behaviors and perceived health status of child care providers. Health behaviors and health status were also examined in relation to caring for children and the providers' perceptions of quality child care. A researcher-developed questionnaire, adapted from Williams, Mason, and Wold (2001), was mailed to a random sample of 1,000 child care providers employed in 49 child care centers in Georgia. Results indicated that, overall, the sample was a health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…In our cumulative risk score, we found that 46% of providers had a risk score of 4, 5 or 6. This result is similar to other studies with child care providers; having a high prevalence of overweight/obesity ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Sharma et al, 2013 ), high prevalence of physical and mental health conditions, poor health status and frequent mentally and physically unhealthy days ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Todd and DeerySchmitt, 1996 , Whitaker et al, 2013 ). This extends the prior literature in that few studies have included family child care home providers as part of their research, but have rather focused on centers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our cumulative risk score, we found that 46% of providers had a risk score of 4, 5 or 6. This result is similar to other studies with child care providers; having a high prevalence of overweight/obesity ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Sharma et al, 2013 ), high prevalence of physical and mental health conditions, poor health status and frequent mentally and physically unhealthy days ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Todd and DeerySchmitt, 1996 , Whitaker et al, 2013 ). This extends the prior literature in that few studies have included family child care home providers as part of their research, but have rather focused on centers.…”
Section: Discussionsupporting
confidence: 91%
“…The daily routines of child care providers are stressful, physically demanding, and include exposure to infectious diseases such as influenza, hepatitis and diarrheal illnesses ( Gratz and Claffey, 1996 ). Among the few studies that describe the health of child care providers, results suggest they have a high prevalence of many health problems and exhibit unhealthy behaviors, including being overweight or obese ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Sharma et al, 2013 ), feeling emotionally strained (depressed, overwhelmed) ( Baldwin et al, 2007 , Gratz and Claffey, 1996 , Todd and DeerySchmitt, 1996 , Whitaker et al, 2013 ), and failing to exercise regularly ( Gratz and Claffey, 1996 ). These findings suggest that it is important to obtain a fuller understanding of the risk profile of child care providers.…”
Section: Introductionmentioning
confidence: 99%
“…While Head Start programs have more standardized organizational structure and financial support compared to center-based programs, the study suggests that many of the workers were still struggling with multiple health issues. Among the few other studies with child care workers, results suggest elevated levels of emotional distress [10], multiple health risk behaviors [11], and increased prevalence of overweight and obesity [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In the same study, the prevalence rates for overweight and obesity were 41 and 18 % respectively [20]. Similarly, a study from Georgia reported that 50 % of female childcare providers were overweight or obese [21]. Most early childhood workers in a study from New Zealand believed that they have good nutrition and perceived their health as good or excellent.…”
Section: Introductionmentioning
confidence: 99%